Use of interferon gamma following prrimary graft failure after hematopoietic stem cell transplantation in a patient with chronic granulomatous disease in a public hospital in Peru: a case report - Ruiz, Pedro (2025)
We present the case of a male patient aged one year and six months, diagnosed with chronic granulomatous disease since the first month of life, due to a mutation in the CYBB gene. Early diagnosis was possible due to a family history of the same disease in an older brother aged 11 years and the detection of the mutation in the mother (carrier). The patient had a history of two hospitalizations. The first lasted five months and was due to a diagnosis of community-acquired pneumonia, complicated by respiratory failure, acute infectious diarrhea due to Pseudomonas aeruginosa and cytomegalovirus infection. The second hospitalization occurred at 11 months of age due to sepsis of gastrointestinal and respiratory origin. The patient received antimicrobial prophylaxis with trimethoprim-sulfamethoxazole, itraconazole and acyclovir, along with monthly intravenous immunoglobulin infusions, with limited response. During the first hospitalization, at five months of age, a hematopoietic stem cell transplant was attempted using his father as the donor; however, 0 % chimerism was achieved. Since October 2024 (at 12 months of age), subcutaneous interferon gamma therapy was initiated—representing the first reported case of its use in Peru. Currently, six months after the initiation of interferon gamma therapy, the patient has not experienced any new infectious episodes. Only three mild adverse reactions were reported following 98 doses. This case demonstrates the clinical utility and safety of interferon gamma in individuals with chronic granulomatous disease. Patients who, for various reasons, are unable to access definitive bone marrow transplantation may receive it in combination with standard antimicrobial prophylaxis.